ANALYZING STUDENTS’ SPEAKING ANXIETY: LEVEL, CAUSES & STRATEGY - Rizka Muftiari Aulia; Muhammad Dalimunte (ELTIN Journal, 2024)
Anxiety is a significant factor that might impede learning a foreign language. This study used qualitative approach. In this study, twenty-five senior high school students and five English teachers participated in this study. Questionnaire and interview were used in this study as the research instrument. The objectives of this study are to investigate the level of anxiety experienced by the students in speaking English, to identify the numerous causes that trigger students’ anxiety in speaking English and to know the English teacher strategies to overcome the anxiety. The results showed that there are three level of anxiety experienced by the students such as very Anxious Level (20%), Anxious Level (23%) and Mildly Anxious level (47%). While, the other students felt relaxed (3%) and very relaxed (7%). In addition, the data also revealed that the factors of students’ anxiety include four aspects such as lack of confidence, lack of Preparation, lack of motivation and fear of making mistake. Finally, the data also found that there are several strategies used by the teacher to overcome the anxiety such as by providing support, playing game, and using question and answer strategies.